2009
DOI: 10.1109/tit.2009.2025529
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Connections Between Pseudocodewords

Abstract: Abstract-The role of pseudocodewords in causing noncodeword outputs in linear programming (LP) decoding, graph cover decoding, and iterative message-passing decoding is investigated. The three main types of pseudocodewords in the literature -linear programming pseudocodewords, graph cover pseudocodewords, and computation tree pseudocodewords -are reviewed and connections between them are explored. Some discrepancies in the literature on minimal and irreducible pseudocodewords are highlighted and clarified, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 18 publications
1
19
0
Order By: Relevance
“…Thus, if one can fully understand configurations on the universal cover and devise a decoder on the universal cover that simultaneously extends both graph cover decoding [10] and min-sum decoding, then one can possibly use the theory of graph covers and graph cover pseudocodewords to better understand computation trees and computation tree pseudocodewords, and, ultimately, the behavior of min-sum decoding. This is precisely what is attempted by the authors and their collaborators in [2]- [4].…”
Section: Introductionsupporting
confidence: 67%
See 1 more Smart Citation
“…Thus, if one can fully understand configurations on the universal cover and devise a decoder on the universal cover that simultaneously extends both graph cover decoding [10] and min-sum decoding, then one can possibly use the theory of graph covers and graph cover pseudocodewords to better understand computation trees and computation tree pseudocodewords, and, ultimately, the behavior of min-sum decoding. This is precisely what is attempted by the authors and their collaborators in [2]- [4].…”
Section: Introductionsupporting
confidence: 67%
“…The authors and their collaborators have shown [1] that with a very basic restriction on our Tanner graph, every normalized graph cover pseudocodeword has a connected realization. The restriction on the Tanner graph is given by…”
Section: Definition 14 (Wibergmentioning
confidence: 99%
“…The iterative message passing algorithm cannot overcome these weaknesses and gets trapped in error patterns which are easily identifiable as erroneous (in LDPC codes), and are thus not valid codewords, but difficult to overcome or correct [1], [2]. These weaknesses were termed trapping sets by Richardson in [3], a summary definition for the patterns on which the message passing algorithm fails for Gaussian channels.…”
Section: Discussionmentioning
confidence: 99%
“…This code has been extensively analyzed. It has a low error floor that appears at E b /N 0 ≈ 5dB at a BER of 10 −12 , that is too low to be efficiently explored using conventional simulations 1 . ( ( ( ( ( ( ( ( ( 4 4 4 A A A A A A A A A G G G G G G G G G G G G G T T T T T T T T T T T T T T w w w w w w w w w w w w w w w w w w w A A A A A A A A A A A A w w w w w w w w w w w w w w w w w w w w w w w w T T T T T T T T T T T T T T !…”
Section: Ldpc Codes On the Gaussian Channelmentioning
confidence: 99%
“…19 To see this, let the active part of a pseudo-codeword be defined as the set of bit nodes corresponding to the support of the pseudo-codeword, along 19 Here and in the following, pseudo-codewords refer to pseudo-codewords as they appear in linear programming (LP) decoding [54], [55] and in the graph-cover-based analysis of message-passing iterative decoding in [22], [23]. For other notions of pseudo-codewords, in particular computation tree pseudo-codewords, we refer to the discussion in [56]. with the adjacent edges and check nodes.…”
Section: A Graph-cycle Analysismentioning
confidence: 99%